Fluorescent Nanoparticle Imaging Allows Noninvasive Evaluation of Immune Cell Modulation in Esophageal Dysplasia - Peiman Habibollahi; Todd Waldron; Pedram Heidari; Hoon Sung Cho; David Alcantara; Lee Josephson; Timothy C. Wang; Anil K. Rustgi; Umar Mahmood (Molecular Imaging)
Esophageal tumors provide unique challenges and opportunities for developing and testing surveillance imaging technology for different tumor microenvironment components, including assessment of immune cell modulation, with the ultimate goal of promoting early detection and response evaluation. In this context, accessibility through the lumen using a minimally invasive approach provides a means for repetitive evaluation longitudinally by combining fluorescent endoscopic imaging technology with novel fluorescent nanoparticles that are phagocytized by immune cells in the microenvironment. The agent we developed for imaging is synthesized from Feraheme (ferumoxytol), a Food and Drug Administration-approved monocrystaline dextran-coated iron oxide nanoparticle, which we conjugated to a near-infrared fluorochrome, CyAL5.5. We demonstrate a high level of uptake of the fluorescent nanoparticles by myeloid-derived suppressor cells (MDSCs) in the esophagus and spleen of L2Cre;p120ctn flox/flox mice. These mice develop esophageal dysplasia leading to squamous cell carcinoma; we have previously demonstrated that dysplastic and neoplastic esophageal lesions in these mice have an immune cell infiltration that is dominated by MDSCs. In the L2Cre;p120ctn flox/flox mice, evaluation of the spleen reveals that nearly 80% of CD45 + leukocytes that phagocytized the nanoparticle were CD11b + Gr1 + MDSCs. After dexamethasone treatment, we observed concordant decreased fluorescent signal from esophageal lesions during fluorescent endoscopy and decreased CyAL5.5-fluorescent-positive immune cell infiltration in esophageal dysplastic lesions by fluorescence-activated cell sorting analysis. Our observations suggest that this translatable technology may be used for the early detection of dysplastic changes and the serial assessment of immunomodulatory therapy and to visualize changes in MDSCs in the esophageal tumor microenvironment.